Antioxidants and lipid peroxidation levels of blood and cervical mucus in cows in relation to pregnancy - Naziroglu, M; Gür, S (M H Schaper Gmbh Co Kg, 2000)
Levels of vitamins A and E, beta carotene and lipid peroxidation product (TBARS) were determined in plasma and cevical mucus of 32 cows. Red blood cell (RBC) reduced glutathione (GSH) and RBC glutathione peroxidase (GSH-Px) activity as well as Vitamin C plasma levels were measured. After taking cervical mucus and blood samples the animals were insemineted artificially. Three month later pregnant (n = 20) and non pregnant (n = 12) cattle were determined. Correlations between investigated parameters and pregnancy rate were performed. In blood plasma, a significant correlation was observed between vitamin A and beta carotene (P < 0.001) as well as Vitamin E (P < 0.05). There was a significant (P < 0.001) correlation in TEARS values of plasma and cervical mucus. However, none of the investigated parameters showed a significant difference between pregnant and non pregnant cows. In conclusion, we did not find any difference and correlation between pregnant and nonpregnant animals concerning the investigated antioxidants. A positive correlation was observed between lipid peroxidation levels of plasma and cervical mucus. Our work provides basic informations about antioxidative parameters under physiological conditions. Further studies should investigate possible correlation between disturbed fertility and antioxidative status of plasma and cervical mucus in clinically healthy cows.
Keywords: vitamin E; beta carotene; cervical mucus; fertility; cow